2008
DOI: 10.2522/ptj.20070233
|View full text |Cite
|
Sign up to set email alerts
|

Process for Applying the International Classification of Functioning, Disability and Health Model to a Patient With Patellar Dislocation

Abstract: The ICF model has been proposed as a framework for developing diagnostic classifications for rehabilitation professionals. The ICF model also should be assessed with regard to whether it provides a useful process for clinical decision making. The ICF model directs practitioners to address patients' problems at the level of the whole person, with modifications made on the basis of health conditions and personal and environmental factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…The literature poorly described the non‐operative management strategies used to treat patients following a patellar dislocation. Whilst authors appropriately discussed immobilisation methods and duration, they only reported that patients were rehabilitated with either thigh strengthening exercises or VMO rehabilitation, whereas the inclusion of glutei and core stability muscle control, muscle flexibility and proprioception exercises may be anticipated in a conservative treatment programme [22, 32, 38, 42]. This is a recurrent limitation in the patellar instability evidence‐base [48].…”
Section: Discussionmentioning
confidence: 99%
“…The literature poorly described the non‐operative management strategies used to treat patients following a patellar dislocation. Whilst authors appropriately discussed immobilisation methods and duration, they only reported that patients were rehabilitated with either thigh strengthening exercises or VMO rehabilitation, whereas the inclusion of glutei and core stability muscle control, muscle flexibility and proprioception exercises may be anticipated in a conservative treatment programme [22, 32, 38, 42]. This is a recurrent limitation in the patellar instability evidence‐base [48].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 10 years, the ICF model has emerged as a popular way to characterize patient functioning in physical therapy (Jette, 2006). The feasibility of using the ICF model in physical therapy case reporting is supported by several examples in the peer reviewed literature (Helgeson and Smith, 2008;Rundell et al, 2009;Rundell and Davenport, 2010;Atkinson and Nixon-Cave, 2011;Furze et al, 2012), as well the existence of an ICF use case manual (Bickenbach et al, 2012). Similar to the adoption of other frameworks for ensuring uniform reporting standards, the ICF model should be explicitly adopted by physical therapy journals as the recommended framework for discussing patient functioning in case reports.…”
Section: Summary Of Recommendationsmentioning
confidence: 99%
“…A few examples are available in the physical therapy case literature, in which the ICF model has been used as a common language for describing patient disablement. For example, Helgeson and colleagues (Helgeson and Smith, ) first described the application of the ICF model to the physical therapy management of an individual with patellar dislocation. However, ICF qualifiers were not present in this paper.…”
Section: Movement Toward Functioning In Biomedical Case Reportingmentioning
confidence: 99%
See 1 more Smart Citation